Survei Kekuatan Otot Lengan terhadap Kemampuan Passing Bawah Putra Kelas V di SD Sains Nusantara - Wildan Maftuh; Khafid Ikhram (Jurnal Kridatama Sains dan Teknologi, 2026)
The underhand passing skill in volleyball is influenced by various components of physical fitness, one of which is arm muscle strength. This study aimed to determine the relationship between arm muscle strength and underhand passing ability among fifth-grade male students at SD Sains Nusantara. This research employed a quantitative approach using a survey method. The participants consisted of all 15 male students in the fifth grade of SD Sains Nusantara. The research instruments included the independent variable (X), namely arm muscle strength, measured using a 30-second push-up test, and the dependent variable (Y), namely underhand passing ability, measured using a 60-second wall volley test. The results showed that the average arm muscle strength was 19.33 repetitions (64.44%), while the average underhand passing score was 25.00 points (83.33%). The findings also indicated a positive relationship between arm muscle strength and underhand passing ability, as students with greater arm muscle strength tended to achieve higher underhand passing scores. It can therefore be concluded that arm muscle strength is associated with underhand passing ability among fifth-grade male students at SD Sains Nusantara, suggesting that improving arm muscle strength may contribute to better underhand passing performance